LINGUACULTURE - AS THE MAIN CONCEPT OF LINGUACULTURAL STUDIES - Butabekova , Durdona; Urinboev, Shakhzod (Наука и инновация, 2023)
This article delves into the foundational concept of linguaculture, exploring the intricate relationship between language and culture. It highlights linguaculture as a pivotal concept in linguacultural studies, emphasizing the mutual influence between language and cultural dynamics. Through comprehensive analysis and theoretical frameworks, the study illustrates how language embodies cultural expressions, values, and societal norms. It also elucidates how culture shapes linguistic patterns and communication styles. The article delves into various linguistic and cultural phenomena, unveiling the profound impact of linguaculture on societal identities, intercultural communication, and the evolving globalized landscape. This scholarly work significantly contributes to the understanding of linguaculture’s centrality in linguacultural studies, offering profound insights into the inseparable nexus between language and culture in shaping human experiences.